2021
DOI: 10.1039/d1cc02494a
|View full text |Cite
|
Sign up to set email alerts
|

Hg3(Te3O8)(SO4): a new sulfate tellurite with a novel structure and large birefringence explored from d10 metal compounds

Abstract: Our explorations of novel inorganic solids with large birefringence in d10 Metal-Te4+-SO42- system afforded four new sulfate tellurites, Ga2(TeO3)(SO4)(OH)2, In2(TeO3)2(SO4)(H2O), Zn4(Te3O7)2(SO4)2(H2O) and Hg3(Te3O8)(SO4). Notably, Hg3(Te3O8)(SO4) exhibits the largest birefringence at...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 40 publications
5
31
0
Order By: Relevance
“…It has been reported that the birefringence of a compound is inversely related to the band gap of the structure. 19,53–56 As shown in Fig. 5, Hg 2 (SeO 3 )(SO 4 ) exhibits the narrowest band gap among the three compounds.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…It has been reported that the birefringence of a compound is inversely related to the band gap of the structure. 19,53–56 As shown in Fig. 5, Hg 2 (SeO 3 )(SO 4 ) exhibits the narrowest band gap among the three compounds.…”
Section: Resultsmentioning
confidence: 87%
“…, Y 2 (Te 4 O 10 )(SO 4 ), 18 Ga 2 (TeO 3 )(SO 4 )(OH) 2 and Hg 3 (Te 3 O 8 )(SO 4 ). 19 It is worth noting that Hg 3 (Te 3 O 8 )(SO 4 ) exhibits the largest birefringence at 532 nm (0.184) and 1064 nm (0.166) in these reported metal sulfate tellurites.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…In addition, tetrahedral groups have a wide UV transmission window, which is beneficial to obtain UV and deep-UV optical compounds . However, compared with π-conjugated genes, the non-π-conjugated tetrahedral genes, like (BO 4 ) 5– , (PO 4 ) 3– , , and (SO 4 ) 2– have T d symmetry, which is not beneficial to generating large optical anisotropy. Therefore, it is urgent to develop suitable methods to improve the optical anisotropy of tetrahedral groups.…”
mentioning
confidence: 99%